2009
DOI: 10.1039/b816196h
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric spin crossover behaviour and evidence of light-induced excited spin state trapping in a dinuclear iron(ii) helicate

Abstract: Reported herein are the synthesis, structural and magnetic characterisation of a dinuclear FeII triple helicate that displays an unprecedented reversible asymmetric high spin to low spin crossover characterised by a thermal hysteresis: indeed the high spin state can be recovered by white light irradiation at 10 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 31 publications
4
40
1
Order By: Relevance
“…This is probably due to the experiment that is only a fast cooling from 300 K to 10 K and not an instant quench, which strongly differs from the thermal-quenching previously performed on an X-Ray diffractometer, showing similar structures between the high temperature and the metastable HS phases [55]. Note that the discrepancy between magnetic and diffraction experiments in term of quenching effect investigation were discussed elsewhere on a similar material [56]. This effect remains however quite surprising since the efficiency of thermal quenching is expected to increase with the decrease of T 1/2 .…”
Section: T(liesst) and T(tiesst) Versus Internal Pressurecontrasting
confidence: 40%
See 1 more Smart Citation
“…This is probably due to the experiment that is only a fast cooling from 300 K to 10 K and not an instant quench, which strongly differs from the thermal-quenching previously performed on an X-Ray diffractometer, showing similar structures between the high temperature and the metastable HS phases [55]. Note that the discrepancy between magnetic and diffraction experiments in term of quenching effect investigation were discussed elsewhere on a similar material [56]. This effect remains however quite surprising since the efficiency of thermal quenching is expected to increase with the decrease of T 1/2 .…”
Section: T(liesst) and T(tiesst) Versus Internal Pressurecontrasting
confidence: 40%
“…One similar shape of T(LIESST) was however described in 2009 on a binuclear compound. This behavior has been explained by a competition between the different states of the binuclear that are HS-HS, HS-LS and LS-LS [56]. Analogy with such conclusions might be performed here due to the presence of two different metallic sites within the materials, those of Fe that can undergo a SCO and those of Mn that do not.…”
Section: Focus On the Thermally-quenched Metastable-statementioning
confidence: 53%
“…Two years later, the Mössbauer and magnetic properties of such complexes with the ClO 4 − counter ion were examined by Garcia and Gütlich [28]. More recently, further studies of such helicates were conducted by Kruger [29,30], employing an oxygen central atom (-O-), identifying the importance of the degree of solvation on the spin transition of these compounds, as well as investigating the light-induced trapping of the excited state. Alternatively, the design and synthesis of coordination cages reported by Fujita [33], showed that the steric nature of the central atom of the ligand (C, S or O) could be manipulated to give subtly different ligand angles, which produced profound changes in the overall supramolecular architecture.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are only a few examples of Fe(II) dinuclear triple helicates that are capable of undergoing a reversible spin transition [25,[28][29][30][31][32], all of which utilise the imidazole-imine moiety. Such compounds are composed of three ligands bridging two metal ion centres in a helical architecture.…”
Section: Introductionmentioning
confidence: 99%
“…The SCO of this system was reinterpreted by Gütlich and co-workers [15]. Very recently, Pelleteret et al reported LIESST (light-induced excited spin state trapping) in a dinuclear Fe II helicate with ligands containing imidazolimine groups [16].…”
Section: Introductionmentioning
confidence: 94%